TRANSFORMASI DIGITAL, KETIMPANGAN PENDAPATAN, DAN KRIMINALITAS DI INDONESIA: SEBUAH KAJIAN EMPIRIS - Ajeng Lestari, Aprima Vista; Agusalim, Lestari (Center for Economic Studies Universitas Katolik Parahyangan, 2025)
The rapid development of digital technology has become a key force in transforming various aspects of life, such as accelerating information access, enhancing economic efficiency, and creating new opportunities. However, this transformation also brings challenges, particularly regarding the unequal distribution of income. Limited access to digital technology can exacerbate income inequality, where only a small portion of the population fully optimizes its benefits while others are left behind. Income inequality, as reflected in the Gini index, indicates an increasingly unequal income distribution and potentially elevates crime rates. This study analyzes the impact of income inequality on crime in the era of digital transformation using a random effect model and panel data from 34 provinces in Indonesia from 2010 to 2022. The findings show that income inequality has a significant positive effect on crime growth, meaning that the greater the income disparity, the higher the crime growth. The interaction between income inequality and internet usage shows a significant negative effect, indicating that a more equitable distribution of digital technology can reduce the impact of income inequality on crime. Additionally, the human development index has a significant positive effect, while the COVID-19 dummy variable has a significant negative effect on crime growth.